CIPP Evaluation of Quranic Program for Students with Disabilities in Inclusive Islamic Education - Fitra Elnurianda; Zurqoni Zurqoni; Siti Kamilah; Rita Sriayu; Abdul Rahim bin Abdul Rahman; Heri Retnawati; Umar Fauzan (Universitas Nurul Jadid, 2025)
This study evaluates the implementation of the UMMI method within the Quranic learning program for students with disabilities at SD Fastabiqul Khairat Samarinda. Utilizing Daniel Stufflebeam’s Context, Input, Process, and Product (CIPP) evaluation framework, this study adopts a qualitative phenomenological design to analyze institutional dynamics, resource capacities, classroom processes, and educational outcomes. Data were systematically gathered through prolonged field observations, semi-structured interviews with the program coordinator, classroom instructors, and shadow teachers, alongside extensive document analysis. The context evaluation reveals a structural tension between standardized institutional performance metrics (a mandatory 90% graduation target) set by central authorities and the individualized requirements of inclusive education. Input evaluation indicates a significant lack of adaptive pedagogical guidelines and non-standardized Quranic recitative competencies among shadow teachers. Process observations show that while individualized instruction is maintained, daily operations are heavily constrained by students' cognitive barriers, speech-motor limitations, and behavioral tantrums. Product evaluation demonstrates that although the program yields profound benefits in fostering spiritual security, emotional regulation, and self-confidence, academic milestones remain significantly delayed. This delay prompts institutional statistical exclusion to safeguard public performance metrics. These findings underscore the critical need to reconstruct flexible assessment matrices, validate shadow teachers' recitative competencies, and transition from rigid standardized metrics to individual progress designs.